The Influence of Islamic Work Ethic and Job Satisfaction on Organizational Commitment: Islamic Educational Institution Evidence - Siswanto Siswanto; Setiani Setiani; Ahmad Syakur (Faculty of Economic and Business, 2019)
The influence of work ethics on employee performance is highly important. There has been indeed contradictive sight on some researches related to religious alliances. This research is aimed at analyzing the direct and indirect influence of Islamic work ethics on organizational commitment through job satisfaction. Data analysis is used path analysis. The sample of the study consists of 70 respondents. The result shows that Islamic work ethics has direct and indirect influence on organizational commitment. The indirect influence of Islamic work ethics on organizational commitment is lower than the direct one. Islamic work ethics can increase organizational commitment indirectly through job satisfaction. Meanwhile, the total indirect influence of Islamic work ethic on organizational commitment is smaller than the direct one. The managerial implication of the current research is that the principal should conduct an ongoing assessment on the work satisfaction of the teachers and employees in order to enhance their organizational commitment.JEL Classification: I23, J28